2018
DOI: 10.1016/j.pmedr.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and chronic kidney disease in the Hispanic community health study/study of Latinos (HCHS/SOL)

Abstract: Hispanics/Latinos are burdened by chronic kidney disease (CKD). The role of acculturation in this population has not been explored. We studied the association of acculturation with CKD and cardiovascular risk factor control. We performed cross-sectional analyses of 13,164 U.S. Hispanics/Latinos enrolled in the HCHS/SOL Study between 2008 and 2011. Acculturation was measured using the language and ethnic social relations subscales of the Short Acculturation Scale for Hispanics, and proxies of acculturation (lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In combination with ROS and MAP, the number of Latinx participants across RADC cohort studies is approaching a total of 500 participants. Latinxs in RADC cohort studies reported low levels of ac-culturation, similar to those found in the HCHS/SOL cohort [97]. Latinxs also reported higher levels of neuroticism and depressive symptoms compared with non-Latinx blacks and whites.…”
Section: Discussionsupporting
confidence: 67%
“…In combination with ROS and MAP, the number of Latinx participants across RADC cohort studies is approaching a total of 500 participants. Latinxs in RADC cohort studies reported low levels of ac-culturation, similar to those found in the HCHS/SOL cohort [97]. Latinxs also reported higher levels of neuroticism and depressive symptoms compared with non-Latinx blacks and whites.…”
Section: Discussionsupporting
confidence: 67%
“…Next we sought to understand the relationship of GMB with acculturation, or adaptation of features of the US environment, which varied across birthplace and relocation age groups (Table 2) [1719]. English language preference was associated with lower Prevotella to Bacteroides ratio and lower fungal Shannon diversity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the HCHS/SOL, lower language acculturation was associated with CKD among older adults (>65 years of age); however, among those with CKD, acculturation measures were not associated with hypertension or diabetes control. 18…”
Section: Social Determinants Of Ckdmentioning
confidence: 99%